EFFECT OF GGC (GEOFOAM GRANULE COLUMN) ON ACCELERATION OF SETTLEMENT IN SOFT SOIL - Adelina Maulidya Firdaus; Yulvi Zaika; As'ad Munawir (Rekayasa Sipil, 2020)
Soft soils has low bearing capacity and high compressibility whichis potentially damage the structure laid above it.An effort is taken to use EPS beads to form GGC will accelerate of consolidation process. The purpose of study to investigate the influence of density and diameters of GGC against strength and settlement. Triaxial test are conducted to identify the shear strength parameter after consolidation test were done. The equivalence value of permeability (kve) is calculated using the Chai Method (2001) by considering smear effect. Test results showed that the settlement of soft soil in 90 degree consolidation reached in short period of time upon for smallest density and largest diameter of GCC.